A Review of the Fiscal Impulse Measure - Mansur, Ahsan (Occasional Papers; Occasional Paper ;, 1986)
This study was prepared jointly by the Fiscal Affairs and Research Departments of the International Monetary Fund. Since the study was made in preparation for the World Economic Outlook exercise of April 1984, all estimates reflect data and analyses as of the end of February 1984.